Endothelial Dysfunction in Psoriasis: An Updated Review - Anyfanti, Panagiota; Margouta, Anastasia; Goulas, Kyriakos; Gavriilaki, Maria; Lazaridou, Elizabeth; Patsatsi, Aikaterini; Gkaliagkousi, Eugenia (Frontiers in Medicine, 2022)
Although psoriasis is predominantly a chronic inflammatory skin disorder, epidemiological data provide a solid link between psoriasis, especially in its more severe forms, and increased risk for cardiovascular morbidity and mortality. Apart from the increased prevalence of traditional cardiovascular risk factors, chronic inflammation appears to act synergistically with the underlying process of endothelial dysfunction toward the development of accelerated atherosclerosis, subclinical vascular injury and subsequently, clinically evident cardiovascular manifestations. Endothelial dysfunction is regarded as an early precursor of atherosclerosis with a predictive value for the development of future cardiovascular events. A thorough understanding of the mechanisms of endothelial dysfunction in psoriasis might pave the path for the development of more accurate cardiovascular risk prediction tools and possible therapeutic targets aiming to alleviate the increased cardiovascular burden associated with the disease. The present review summarizes the available evidence about the role of chronic inflammation and other important pathophysiological mechanisms involved in the development of endothelial dysfunction in psoriasis. An overview of studies implementing the most widely applied circulating and vascular biomarkers of endothelial dysfunction in psoriasis patients will be provided, and the impact of systemic psoriasis treatments on endothelial dysfunction and patients’ cardiovascular risk will be discussed.